Crescimento e qualidade nutritiva da planta de soja (Glycine max (L.) Merril) - Souza dos Santos, Osmar; Vieira, Clibas (Revista Ceres, 2025)
The nutritive values of dry and green hay of ‘Hardee’ and ‘Santa Rosa’ soybean cultivars were evaluated at Santa Maria, State of Rio Grande do Sul. Cuttings were made during the vegetative and reproductive stages, the plants cut just above the soil surface.